Genetic analysis of parental lines and identification of heterotic hybrid combinations in rice (Oryza sativa L.) - Mohan, Y Chandra; Krishna, L; Singh, TV; Babu, T Kiran; Varma, NRG; Ramana, M Venkata (ORYZA-An International Journal of Rice, 2022)
Thirty hybrids along with their parents (B and R lines) and standard checks viz., MTU 1001 and 27P63 were evaluated for grain yield and related traits to study combining ability and heterosis in rice. The mean performance of the hybrids for most of the characters was found higher than that of parents. The analysis of variance revealed significant differences among lines, testers and hybrids for most of the characters studied. SCA variances were found lower than GCA variances for most of the characters and average degree of dominance was far from unity indicating the predominance of additive gene action for these traits. However, for effective bearing tillers and spikelet fertility the average degree of dominance was very near to unity inferring the predominance of non-additive genetic components for these traits. The gca effects revealed that the lines, RNR 25783 and RP 5980-109-12-9-27 had significant gca effects in desired direction for yield and yield attributing traits whereas the tester, CMS 59A was a good general combiner. SCA effects showed that the hybrid, JMS 13A × RNR 19361 was found to be good specific combiner for grain yield per plant and spikelet fertility. Similarly, the hybrids, CMS 59A × SYE 503-78-34-2, CMS 46A × WGL 347 and JMS 13A × RP 5980-109-12-9-27 were identified as good specific combiner for grain yield and yield contributing characters. Based on heterotic estimates, five hybrids viz., CMS 59A × RNR 25783, CMS 59A × WGL 14, JMS 13A × RNR 25783, CMS 59A × RNR 25776, JMS 13A × RP 5980-109-12-9-27 were identified as promising with more than 5% and 20% yield advantage over hybrid and varietal checks, respectively.